Penggunaan Media Interaktif Berbasis Website Wordwall dalam Pembelajaran tentang Macam-macam Kegiatan Ekonomi Masyarakat untuk Meningkatkan Hasil Belajar Siswa Pembelajaran IPAS di Kelas V SD GMIT Oebobo - Upa, Nora Cahyani Aprilia; Taneo, Silverster; Adoe, Treesly Y. N (ARZUSIN, 2025)
This study is motivated by the low student learning outcomes in IPAS learning, especially the material of various kinds of community economic activities in class V SD GMIT Oebobo which is due to the use of learning media that is less varied so that it triggers student boredom and difficulty in understanding learning. The formulation of the problem in this study is how to improve student learning outcomes on the material of various kinds of community economic activities through the use of interactive media based on the wordwall website. Because the purpose of this study is to improve student learning outcomes in the material of various kinds of community economic activities through the use of interactive media based on the wordwall website. The type of research used in this research is Classroom Action Research which is carried out in 2 cycles, where each cycle consists of 4 stages, namely 1) Planning, 2) Implementation, 3) Observation, and 4) Reflection. The data collection techniques were observation, tests, and documentation studies while the data analysis was descriptive analysis. The results showed that the percentage of student learning outcomes completed in cycle I of 34% increased to 100% in cycle II of the 26 student test results analyzed. The use of interactive media in this lesson also improved the criteria for student activity which in cycle I was in the sufficient criteria increased to very good in cycle II and the criteria for teacher activity which in cycle I was in the good criteria increased to very good in cycle II. Thus, the use of interactive media based on wordwall website in learning about various economic activities of the community can improve student learning outcomes of IPAS learning in grade V of GMIT Oebobo Elementary School.